2019
DOI: 10.1002/prp2.466
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of GPR139 reveals ways to create gain or loss of function receptors

Abstract: GPR139 is a Gq‐coupled receptor activated by the essential amino acids L‐tryptophan (L‐Trp) and L‐phenylalanine (L‐Phe). We carried out mutagenesis studies of the human GPR139 receptor to identify the critical structural motifs required for GPR139 activation. We applied site‐directed and high throughput random mutagenesis approaches using a double addition normalization strategy to identify novel GPR139 sequences coding receptors that have altered sensitivity to endogenous ligands. This approach resulted in GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Further research into the interaction between GPR139 and the opioid system found that this receptor activation led to anti-opioid activity in C. elegans . This was conserved in rodents, where deletion of GPR139 in mice potentiated opioid-induced inhibition of neuronal firing (Wang, Lee, Shih, et al, 2019). These data were further corroborated by electrophysiological data from GPR139 KO mice medial habenula neurons, where GPR139 receptor signalling was suggested to prevent μ-opioid receptor-mediated neuronal inhibition via G q/11 coupling (Stoveken et al, 2020).…”
Section: Gpr139supporting
confidence: 53%
“…Further research into the interaction between GPR139 and the opioid system found that this receptor activation led to anti-opioid activity in C. elegans . This was conserved in rodents, where deletion of GPR139 in mice potentiated opioid-induced inhibition of neuronal firing (Wang, Lee, Shih, et al, 2019). These data were further corroborated by electrophysiological data from GPR139 KO mice medial habenula neurons, where GPR139 receptor signalling was suggested to prevent μ-opioid receptor-mediated neuronal inhibition via G q/11 coupling (Stoveken et al, 2020).…”
Section: Gpr139supporting
confidence: 53%
“…By combining in silico and in vitro mutagenesis, they identified a common binding pocket consisting of a hydrophobic region deeply buried between F109 3x33 , H187 5x43 and W241 6x48 , and a proximal polar region enclosed by N271 7x38 , R244 6x51 and E108 3x32 (Figure ) . The binding site was confirmed by Wang et al, who also identified a less buried hydrophobic binding site defined by V76 2x73 , F79 2x56 , I104 3x28 , V83 2x60 and I80 2x57 shared by larger GPR139 agonists . They furthermore identified several series of human GPR139 mutations resulting in gain, reduction or loss of function.…”
Section: Gpr139 Receptor Agonist Binding Sitementioning
confidence: 78%
“…Another set of mutations impact the transmembrane helices structure and thus might change the common ligand binding site or the ability to bind G proteins. The authors speculate that the last two set of mutations have a structural impact on GPR139 function …”
Section: Gpr139 Receptor Agonist Binding Sitementioning
confidence: 99%